Wood-derived biochar influences nutrient use efficiency of heavy metals in spinach (spinacia oleracea) under groundwater and wastewater irrigation - Ghori, Sadaf Aslam; Gul, Shamim; Tahir, Saniya; Sohail, Meenah; Batool, Saira; Shahwani, Muhammad Naeem; Bano, Gul; Butt, Mujeeb-ur-Rehman (Journal of Environmental Engineering and Landscape Management, 2019)
Present study analysed the influence of slow-pyrolyzed wood-derived biochar on growth performance and heavy metal accumulation in the leaves of spinach grown under groundwater and wastewater irrigation. Biochar was applied in soil as 5% (~30 t·ha−1) and 10% (~60 t·ha−1) amendment. According to results, plant biomass was significantly higher under wastewater than groundwater irrigation. Biochar amendment increased significantly the aboveground plant biomass and root biomass and promoted water use efficiency (WUE). Under groundwater irrigation, biochar amendment at 10% application rate, increased the leaf area index (P < 0.05), while amendment of biochar at all application rates significantly reduced leaf area index under wastewater irrigation (P < 0.05). Application of biochar also reduced accumulation of rhizosphere soil around roots under wastewater irrigation, indicating less exudate production in the rhizosphere of plants. Biochar significantly reduced the concentration of copper (Cu) in under wastewater irrigation. Biochar increased the nutrient use efficiency (NUE) of plants for zinc (Zn) and Cu under wastewater irrigation.